The Influence of Financial Compensation, Work Environment And Psychological Factors On The Work Ability Of PT. Red and White Cement Bengkulu Branch - Neng Desti Saklira Niraini; Tezar Arianto (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
The title of this research is the influence of financial compensation, work environment factors, and psychological factors on the work ability of employees at PT. Semen Merah Putih Bengkulu Branch. This study used a sample of 47 employees, namely 10 staff members, 13 production staff and 7 technicians, the results of data processing and discussion of the results of data processing. characteristics of respondents, classical assumption test, description of respondents' responses, multiple linear regression analysis, coefficient of determination, t test and F test. ), a value close to one means that the independent variables provide almost all the information needed to predict the variation of the dependent variable from the results of hypothesis testing. The t test is a test to determine the significance of the effect of the independent variable on the dependent variable partially (alone) and considers the other dependent constant